ENDOSKOPIK CHURRA JARROHLIGI: AN’ANAVIY USULLARGA NISBATAN INNOVATSION YONDASHUV (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Endoscopy is a method of visualizing the body using a flexible tube with a small camera and a light source at its end. This instrument is called an endoscope. The endoscope is inserted through a natural body opening or a small incision. There are many types of endoscopes, each named according to the organs or areas they are used to examine.Endoscopic hernia repair is a minimally invasive procedure used to treat hernias by using an endoscope to view the internal area and correct the defect. Unlike traditional open surgery, this type of endoscopy requires only small incisions, leading to faster recovery and reduced postoperative pain.